Advances in Pediatric Acute Kidney Injury Prevention and Early Diagnosis - Nicolau,Beatriz (2022)
ABSTRACT Acute kidney injury (AKI) is frequent in critically ill neonates, children, and adolescents, but it is still underdiagnosed and referral to follow-up at the Pediatric Nephrology Clinic is scant. Nowadays, most pediatric studies use Kidney Disease Improving Global Outcomes (KDIGO) criteria for AKI diagnosis. These criteria are based on the elevation of serum creatinine levels and on the decrease in urine output and they correlate with a higher need for kidney replacement therapy and a higher risk of death. Nonetheless, the KDIGO definition of AKI has several limitations, which may be overcome by the simultaneous use of novel biomarkers, particularly urinary neutrophil gelatinase-associated lipocalin (NGAL). The latter is already available in clinical practice and it is a useful tool to identify AKI earlier and to establish the prognosis. The most common AKI etiologies in the pediatric population are the prerenal causes, namely kidney hypoperfusion due to hypovolemia and peripheral vasodilation in the context of sepsis. Exposure to nephrotoxic drugs has been rising as a primary cause of AKI. Decreasing the use of nephrotoxic drugs whenever clinically possible, monitoring the serum levels of these medications, and adjusting its doses can significantly reduce AKI incidence. Finally, it is important to recognize that AKI is not a completely reversible phenomenon and long-term sequelae are seen in up to 70% of affected children. These sequelae include progression to chronic kidney disease, which accentuates the need for follow-up after an AKI episode. In conclusion, it is essential to improve awareness in the Pediatric community for AKI in order to prevent it, rapidly identify it and establish reno-protective measures, which will improve its long-term prognosis. This review will focus on current definitions, epidemiology and most common etiologies, and it will also discuss strategies to improve pediatric AKI prevention, early diagnosis and follow-up.